Cohesive Devices Used in English Scientific Articles: Comparative Study Across Groups of Indonesian, Malaysian, and Native English Writers - Nanik Sri Rahayu; Sukarsono Sukarsono; Daniar Jauhar Alam (IAIN MADURA, 2022)
In every piece of writing, cohesive devices play an important role in interconnecting the writer's ideas in such a way so that they are logically unified and coherent. However, employing cohesive devices in scientific articles is not always easy for authors who learn English as a foreign language, like Indonesians as well as their Asian counterparts. This current study attempts to look into the compared uses of cohesive devices in English scientific articles written by three different groups, namely Indonesian, Malaysian, and Native English speakers. The data on cohesive devices were collected from articles written in English by different Indonesian writers and from articles written by different Native English authors published in several international journals. The data analysis was carried out quantitatively by identifying and classifying them based on the taxonomy proposed by Halliday and Matthiessen. Descriptive statistics and One-Way ANOVA were also employed in this study. This study revealed that native and non-native writers employed different patterns of cohesive devices. Although Indonesian and Malaysian represent similar distribution patterns at the relatively equivalent level of English proficiency, it does not determine a completely general pattern of cohesive distribution in the reality of writing practice.